Hampshire introduction - Thorn, Frank; Thorn, Caroline; Munby, Julian (The University of Hull)
The introduction discusses the state of the manuscript for the county and the hypotheses on the Domesday Survey and the making of Domesday Book to which it has given rise; the Hundreds, their rubrication, order, and revised name-forms; the New Forest; the editorial history of earlier versions of the notes, and the current state of the revision. Some material in this introduction derives from the original printed edition published by Phillimore (1982) and edited by Julian Munby.